The Effects of Interlocal Collaboration on Local Economic Performance: Investigation of Korean Cases - Eunok Im (European Regional Science Association (ERSA), 2015)
Collaboration among regional/local governments becomes more important for successful local economic development. It has emerged as an alternative to traditional competition-based strategies for local economic development. This study explores the degree of collaboration among local governments in the partnership and its impacts on local economic performance, using nation-wide survey results of 112 local government partnerships for economic development in Korea. Factor analysis identifies three key factors for the degree of interlocal collaboration: (1) commitment to mutual relationships and goals, (2) the quality of communication to build consensus among participants, and (3) the effectiveness of formal joint meetings, as a sub-dimension of communication. The multivariate regressions of three factors on contextual attributes (resource dependence on partners and geographical proximity), relational attributes (social/political similarity, perceived competitive relation, and trust in partners), and institutional attribute (the level of institutionalization) report interesting findings. Trust in partners and the level of institutionalization for the partnership turn out to be the most important factors affecting the level of commitment and the quality of communication in collaboration processes. On the other hand, resource dependence on partners and geographical proximity positively affect only formal joint meeting operation. Using the Baron and Kenny?s three-step hierarchical regression analysis, this study finds that the degree of collaboration mediates the relationship between resource dependence, trust, and the level of institutionalization and local governments? strategic performance. However, it does not show any associations with direct economic performance measures?i.e., effectiveness and efficiency of a collaborative project that might be more influenced by, and thus hardly disentangled from, other various external economic/political factors. It implies that although a high quality collaboration process cannot guarantee the success of project itself, it entails participants? learning (i.e., accumulation of knowledge and experience) that may contribute to innovation and better economic performance in subsequent collaborative projects.
Keywords: 330; degree of collaboration; local economic development; strategic performance